A Pilot Study: The Efficacy of Virgin Coconut Oil as Ocular Rewetting Agent on Rabbit Eyes - Mutalib, Haliza Abdul (Evid Based Complement Alternat Med, 2015)
Purpose. An open-label pilot study of virgin coconut oil (VCO) was conducted to determine the safety of the agent as ocular rewetting eye drops on rabbits. Methods. Efficacy of the VCO was assessed by measuring NIBUT, anterior eye assessment, corneal staining, pH, and Schirmer value before instillation and at 30 min, 60 min, and two weeks after instillation. Friedman test was used to analyse any changes in all the measurable variables over the period of time. Results. Only conjunctival redness with instillation of saline agent showed significant difference over the period of time (P < 0.05). However, further statistical analysis had shown no significant difference at 30 min, 60 min, and two weeks compared to initial measurement (P > 0.05). There were no changes in the NIBUT, limbal redness, palpebral conjunctiva redness, corneal staining, pH, and Schirmer value over the period of time for each agent (P > 0.05). Conclusion. VCO acts as safe rewetting eye drops as it has shown no significant difference in the measurable parameter compared to commercial brand eye drops and saline. These study data suggest that VCO is safe to be used as ocular rewetting agent on human being.